Modified gemcitabine plus nab‐paclitaxel regimen in advanced pancreatic ductal adenocarcinoma. (9th June 2020) - Rogers, Jane E.; Mizrahi, Jonathan D.; Xiao, Lianchun; Mohindroo, Chirayu; Shroff, Rachna T.; Wolff, Robert; Varadhachary, Gauri R.; Javle, Milind M.; Overman, Michael; Fogelman, David R.; Raghav, Kanwal P. S.; Pant, Shubham; et al.
Abstract: Background: Gemcitabine (GEM) plus nab‐paclitaxel (NabP) (GEM 1000 mg/m 2 IV over 30 minutes + NabP 125 mg/m 2 IV given days 1, 8, and 15 every 28 days) is one of the two standard of care combination therapies for metastatic pancreatic ductal adenocarcinoma (PDAC). Our cancer center has utilized GEM‐NabP given every two‐weeks due to tolerability and patient convenience. Here, we review the safety and efficacy of this modified regimen. Methods: Metastatic PDAC patients (pts) who initiated front‐line or second‐line GEM‐NabP during 2013‐2017 were retrospectively reviewed. Primary objective was overall survival. Secondary objectives were disease control rate, progression‐free survival, and the incidence of dose delays and/or adjustments. Results: From a total of 235 patients, 140 pts received GEM‐NabP front‐line while 95 pts received GEM‐NabP second‐line. Median dosing was 600 mg/m 2 at fixed‐dose rate for GEM and 125 mg/m 2 for NabP given predominantly ( 90%) every two‐weeks. Eastern Cooperative Group performance status of 0 and 1 pts had front‐line OS of 12.7 and 9.6 months and when given second‐line had OS of 8 months and 7.3 months, respectively. ECOG 0 and 1 pts had front‐line progression‐free survival (PFS) of 5.3 months and 2.8 months and second‐line PFS was 3.5 months and 2.4 months, respectively. Treatment was well tolerated with limited dose modifications. Conclusion: Our analysis revealed safety with every two‐week low dose GEM‐NabP while maintaining efficacy. Patient schedule convenience should factor into metastatic incurable malignancies. We suggest the use of every two‐week GEM‐NabP particularly in patients desiring a modified schedule. Abstract : Our real‐world data, outside the context of a clinical trial, suggests that every two‐week Gem‐NabP can be administered safely without compromising efficacy in patients with metastatic pancreatic adenocarcinoma (PDAC). In particular, the alternate (bi‐weekly) dosing regimen showed low rates of grades 3 and 4 toxicities and no treatment‐related deaths. This regimen is better tolerated than weekly Gem‐NabP, is convenient, and allows similar palliative benefits to patients with metastatic PDAC.